In Vitro Fertilization Outcomes in Donor Oocyte Cycles Compared to the Autologous Cycles in the Poseidon 4 Group of Poor Ovarian Responders - Jelena Havrljenko; Vesna Kopitovic; Aleksandra Trninic Pjevic; Stevan Milatovic; Sandro Kalember; Filip Katanic; Tatjana Pavlica; Nebojsa Andric; Kristina Pogrmic-Majkic (Medicina)
Background and Objectives: POSEIDON 4 (P4) patients face the most adverse outcomes among poor responders. Oocyte donation has overcome unsatisfactory live birth rates (LBRs) in P4 patients and has become an indispensable approach. However, many patients refuse oocyte donation despite poor live birth likelihood using autologous oocytes. This study aimed to determine clinical outcomes and live birth chances in P4 patients using autologous and donated oocytes. We also identified influencing factors of fertility outcome in P4 patients who underwent donor cycles. Materials and Methods: Retrospective data of 345 P4 patients who explored the first ovarian stimulation cycle (control group) were compared to 105 patients who failed to conceive and underwent repeated autologous ovarian stimulations with an increased starting gonadotropin dose and 100 unpregnant patients who received donated oocytes. Univariate analysis was used to identify prognostic factors of oocyte donation outcomes in P4 patients. Results: LBRs were significantly higher in the donor oocyte group. A higher number of retrieved and good-quality oocytes without differences in the blastocyst number and LBRs were found in the autologous patient group with adjusted gonadotropin dose compared to the control group. Univariate analysis showed that oocyte and embryo quality as well as blastocyst development had a positive impact on live birth in the donor patient group. Conclusions: Autologous in vitro fertilization (IVF) retreating and oocyte donation should be strongly advised for poor-prognosis P4 patients. Still, efforts in tailoring ovarian stimulation to obtain higher oocyte and embryo numbers in autologous cycles should be continued.